TRADISI MALAMANG KHAS PARIAMAN PADA ACARA MAULID NABI MUHAMMAD S.A.W DI KOTA PEKANBARU - Rosi Restyana; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Malamang tradition or in Indonesian that is making lemang is a culture that has grown and developed in the Minangkabau community, especially the people of Pariaman. Malamang is a way of cooking using bamboo media which is then grilled over the embers. Malamang culture was first introduced by Sheikh Buhanuddin to the people of Pariaman when he broadcast Islam in the Ulakan area. Until now, the tradition of Malamang is still carried out by the people of Pariaman who adhere to the Syathariyah Order, namely the traditional Islamic school that was brought by Sheikh Burhanuddin. Malamang tradition is usually carried out in religious activities in Pariaman, such as the birthday of the Prophet and the ceremony of death. In the Pariaman community calendar, the Malamang tradition is usually carried out on the month of Mawlid, namely, the month of Rabiul Awal, Rabiul Akhir and Jumadil Awal. In addition, it is also done in the month of Sya'ban, which in the Pariaman community calendar is known as the Lamang month. Some of the Pariaman people who migrated to Pekanbaru City also carried out this tradition during the Birthday of the Prophet Muhammad S.A.W. In this study, the researchers examined how the implementation of the evening tradition in the Prophet Muhammad's Birthday Celebration was typical of Pariaman in the City of Pekanbaru and what changes took place in the tradition. In this study the researchers used social system theory and social change, with the number of respondents as many as 6 people consisting of Pekanbaru PKDP Representative, Alim Ulama, Majlis Taklim Representative, local mosque committee, community leaders, and the Pariaman community residing in Pekanbaru City. The results of this study indicate that the tradition of Malamang at the celebration of the Birthday of the Prophet Muhammad in Pariaman in Pekanbaru City has undergone changes in terms of its implementation.  Keywords: Malamang, Ascension of the Prophet, Change